Vesicular stomatitis virus-based vaccine targeting plasmodium blood-stage antigens elicits immune response and protects against malaria with protein booster strategy - Sun, Yifan; Shi, Xiaodan; Lu, Feng; Fu, Haitian; Yin, Yi; Xu, Jiahui; Jin, Cheng; Han, Eun-taek; Huang, Xuan; Chen, Yongquan; Dong, Chunsheng; Cheng, Yang (Frontiers in Microbiology, 2022)
Merozoite invasion of the erythrocytes in humans is a key step in the pathogenesis of malaria. The proteins involved in the merozoite invasion could be potential targets for the development of malaria vaccines. Novel viral-vector-based malaria vaccine regimens developed are currently under clinical trials. Vesicular stomatitis virus (VSV) is a single-stranded negative-strand RNA virus widely used as a vector for virus or cancer vaccines. Whether the VSV-based malarial vaccine is more effective than conventional vaccines based on proteins involved in parasitic invasion is still unclear. In this study, we have used the reverse genetics system to construct recombinant VSVs (rVSVs) expressing apical membrane protein 1 (AMA1), rhoptry neck protein 2 (RON2), and reticulocyte-binding protein homolog 5 (RH5), which are required for Plasmodium falciparum invasion. Our results showed that VSV-based viral vaccines significantly increased Plasmodium-specific IgG levels and lymphocyte proliferation. Also, VSV-PyAMA1 and VSV-PyRON2sp prime-boost regimens could significantly increase the levels of IL-2 and IFN-γ-producing by CD4+ and CD8+ T cells and suppress invasion in vitro. The rVSV prime-protein boost regimen significantly increase Plasmodium antigen-specific IgG levels in the serum of mice compared to the homologous rVSV prime-boost. Furthermore, the protective efficacy of rVSV prime protein boost immunization in the mice challenged with P. yoelii 17XL was better compared to traditional antigen immunization. Together, our results show that VSV vector is a novel strategy for malarial vaccine development and preventing the parasitic diseases.